The Role of Early Mobilization Post-Cesarean in Speeding Up Wound Healing (Proceedings OPTIMAL, 2025)
Post Sectio Caesarea (SC) mothers are advised to mobilize, Post Sectio Caesarea (SC) mobilization aims to accelerate wound healing, improve circulation, prevent venous stasis, support optimal respiratory function, improve digestive function, reduce post-surgical complications. The purpose of this study was to determine the relationship between early mobilization after Caesarean section and the acceleration of surgical wound healing in postpartum mothersThis study design uses the Correlational Survey method. A population of 39 postpartum mothers with the Simple Random Sampling technique obtained 36 respondents. The research data was taken using observation and interviews. After being tabulated, the data was analyzed using the Chi Square Test with a significance level of p-value